RETENTION OF 7Be IN THE LUNGS FOLLOWING INTAKE BY INHALATION. Issue 2 (28th July 2017) - Aviv, O; Spitz, H B; Datz, H; Halfon, S; Yungrais, Z; Koch, J
Abstract: Several workers were internally exposed to 7 Be particles following their dispersion in air from a damaged electrodeposited source. A series of in vivo measurements performed with one worker up to 108 days post exposure determined that retention of 7 Be in the thoracic region of the respiratory tract was best described by a two-component exponential function with half-lives of ~0.4 and ~109 days. The initial deposition in the thoracic region was estimated to be 6.8 kBq. The concentration of 7 Be in single void urine samples collected from this worker up to 3 days post intake ranged from 1 to 10 Bq/l. In the absence of specific knowledge about the physical and chemical characteristics of the inhaled particles, the committed effective dose was estimated to be 0.3 μSv.